1986
DOI: 10.1159/000132315
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonemal complexes in Gerbillidae: probable role of intercalated heterochromatin in gonosome-autosome translocations

Abstract: A study of sex chromosomes and synaptonemal complexes in male specimens of Gerbillus chiesmaní, G. nigeriae, G. hoogstrali, and Taterillus pygargus is reported. In each of these Gerbillidae species there are two or three translocations of autosomes with X and Y chromosomes. Analysis of mitotic chromosomes consistently shows the presence of constitutive heterochromatin on the der t(X;autosome) at the X-autosome junction and on the der t(Y;autosome). Analysis of the synaptonemal complexes shows the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 13 publications
3
36
0
1
Order By: Relevance
“…However, the ends of sex chromosome AEs are distally connected at the beginning of diplotene ( Figure 2D and 2D9). This contact may involve any of the ends of each sex chromosome with the other sex chromosome or even the two tips of each chromosome, as shown for sex chromosomes of other species of Gerbillidae [30,31,33]. Nevertheless, at late diplotene the four chromosome ends are always connected ( Figure 2E and 2E9).…”
Section: Author Summarymentioning
confidence: 77%
See 3 more Smart Citations
“…However, the ends of sex chromosome AEs are distally connected at the beginning of diplotene ( Figure 2D and 2D9). This contact may involve any of the ends of each sex chromosome with the other sex chromosome or even the two tips of each chromosome, as shown for sex chromosomes of other species of Gerbillidae [30,31,33]. Nevertheless, at late diplotene the four chromosome ends are always connected ( Figure 2E and 2E9).…”
Section: Author Summarymentioning
confidence: 77%
“…This situation is especially well characterized in marsupials [24][25][26][27][28], in which we have recently reported that a particular structure formed by SC proteins, called dense plate, is involved in maintaining the association of the X and Y chromosomes from pachytene until they segregate at anaphase I [29]. The lack of synapsis has also been reported in some species of eutherian mammals, especially among gerbils and voles [30][31][32][33][34]. In these species sex chromosomes do not form SC, but they are associated during first meiotic prophase and segregate properly during first meiotic division.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Species with unique chromosomal structure such as Gerbil (WAHRMAN etal. 1983;RATOMPONIRINA et al 1986) and Palearctic hamsters (SPYROPOULOS et al 1982), or the common shrew (BoRODIN 1991) have been of particular value. The latter study which detailed the pairing of a Robertsonian translocation and polymorphic Y chromosomes highlights such an informative examination.…”
Section: Introductionmentioning
confidence: 99%